Economic Ripple Effects of Large-Scale Basalt Enhanced Weathering in the Philippines - Kathleen B. Aviso; Maria Victoria Migo-Sumagang; Czarina Alessandra Ramos; Raymond R. Tan (Chemical Engineering Transactions)
Carbon dioxide removal using negative emissions technologies will be needed to achieve net zero greenhouse gas emissions. Enhanced weathering is a negative emissions technology that relies on the acceleration of natural geochemical reactions between alkaline rocks or minerals with carbon dioxide and water. It results in the permanent sequestration of carbon as bicarbonate ions in runoff water. Under some conditions, this technique can also give secondary co-benefits, such as improving the suitability of acidic soil for agriculture. However, large-scale enhanced weathering will require ramping up the activity in the mining, transportation, and electricity generation sectors. In this work, the potential economic effects of large-scale basalt-enhanced weathering in the Philippines are estimated using input-output analysis. The results show that offsetting 20 % of the country's carbon dioxide emissions requires substantial direct increases in quarrying, land transport, and power generation, coupled with smaller changes in other sectors via indirect ripple effects.